Conserved Lysine Acetylation within the Microtubule-Binding Domain Regulates MAP2/Tau Family Members. - Andrew W Hwang (PLoS ONE, 2016)
Lysine acetylation has emerged as a dominant post-translational modification (PTM) regulating tau proteins in Alzheimer's disease (AD) and related tauopathies. Mass spectrometry studies indicate that tau acetylation sites cluster within the microtubule-binding region (MTBR), a region that is highly conserved among tau, MAP2, and MAP4 family members, implying that acetylation could represent a conserved regulatory mechanism for MAPs beyond tau. Here, we combined mass spectrometry, biochemical assays, and cell-based approaches to demonstrate that the tau family members MAP2 and MAP4 are also subject to reversible acetylation. We identify a cluster of lysines in the MAP2 and MAP4 MTBR that undergo CBP-catalyzed acetylation, many of which are conserved in tau. Similar to tau, MAP2 acetylation can occur in a cysteine-dependent auto-regulatory manner in the presence of acetyl-CoA. Furthermore, tubulin reduced MAP2 acetylation, suggesting tubulin binding dictates MAP acetylation status. Taken together, these results uncover a striking conservation of MAP2/Tau family post-translational modifications that could expand our understanding of the dynamic mechanisms regulating microtubules.